Direct Arylation in the Presence of Palladium Pincer Complexes - Garazi Urgoitia; Maria Teresa Herrero; Fátima Churruca; Nerea Conde; Raul SanMartin (Molecules, 2021)
Direct arylation is an atom-economical alternative to more established procedures such as Stille, Suzuki or Negishi arylation reactions. In comparison with other palladium sources and ligands, the use of palladium pincer complexes as catalysts or pre-catalysts for direct arylation has resulted in improved efficiency, higher reaction yields, and advantageous reaction conditions. In addition to a revision of the literature concerning intra- and intermolecular direct arylation reactions performed in the presence of palladium pincer complexes, the role of these remarkably active catalysts will also be discussed.